(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
The choice of contraceptive methods by breastfeeding mothers is a complex decision influenced by various psychosocial and cultural factors. This study aims to explore the perceptions and experiences of breastfeeding mothers in selecting contraceptive methods. Using a qualitative case-study design, the research involved five breastfeeding mothers residing in Parak Karakah, East Padang District. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The findings revealed key themes: (1) perceptions of contraceptive safety for infants, (2) experiences with contraceptive information, (3) anxieties about contraceptive side effects, (4) the role of husbands and social environment, (5) practices and strategies in method selection, and (6) access to healthcare services. These results highlight the need for improved family planning counseling with a more communicative and educational approach, greater involvement of husbands in decision-making, and the utilization of digital media as an effective educational tool.